Understanding Multicultural Education: Perceptions of Prospective Teachers at IAIS (Institut Agama Islam Sultan Muhammad Syafiuddin) Sambas - Barella, Yusawinur; Sulaiman, Sulaiman (Universitas Tanjungpura, 2025)
This study explores the perceptions of prospective teachers at IAIS (Institut Agama Islam Sultan Muhammad Syafiuddin) Sambas regarding multicultural education. Employing a quantitative approach, data were gathered using questionnaires distributed to 100 prospective teachers enrolled in the 2nd, 4th, and 6th semesters across five study programs: Indonesian Language Education, Mathematics Education, Islamic Religious Education, Early Childhood Islamic Education, and Madrasah Ibtidaiyah Teacher Education. The total population consisted of 272 students, and the response rate to the survey was 76%. The collected data was analyzed statistically to understand the relationships between various demographic and educational variables. Key findings indicated that prospective teachers generally possess positive perceptions of multicultural education and recognize its importance in fostering inclusive learning environments. However, gaps identified in knowledge about specific multicultural education courses and diverse backgrounds suggest areas for further development in teacher training programs.